E-Justice in Ecuador: Inclusion of ICTs in the Administration of Justic - Sacoto Romo, María Carolina (2021)
The irruption of new technologies has placed us in what is known as the 4.0 in-dustrial revolution; they have had an impact on every aspect of our private lives as well as on public administration, including Justice. Today, there is already a new concept that was born from the introduction of ICTs to law: e-justice. In this context, this article aims, firstly, to place the administration of justice within the framework of what is considered the latest industrial revolution, then it will try to define e-justice taking into account the advantages that its implementation re-presents to approach the contribution of technological innovations to e-justice in Ecuador based on four core uses of ICTs related to the administration of justice: in-formation, management, relationship and decision, according to the classification made by Pere Fabra. The analysis will be carried out from a descriptive and critical perspective, considering regulations in force as well as existing advances in other countries. The methodology of this work is qualitative, theoretical exploratory and are intented as results the progress as well as the challenges of the implementation of ICTs in the administration of justice in Ecuador